Does Presence of a Median Lobe Affect Perioperative Complications, Oncological Outcomes and Urinary Continence Following Robotic-assisted Radical Prostatectomy? - Hamidi, Nurullah; Atmaca, Ali Fuat; Canda, Abdullah Erdem; Keske, Murat; Gok, Bahri; Koc, Erdem; Asil, Erem; Ardicoglu, Arslan (Urology Journal, 2018)
Purpose: To evaluate of the presence of a median lobe(ML) affect perioperative complications, positive surgical margins(PSM), biochemical recurrence(BCR) and urinary continence(UC) following robotic-assisted radical prostatectomy(RARP). Materials and Methods: Data of 924 consecutive patients who underwent RARP for prostate cancer (PCa) and who have at least 1-year follow-up were evaluated retrospectively. All patients were divided into two groups: Group 1(n=252) included patients with ML and Group 2 (n=672) included patients without ML. The primary endpoint of this study was to compare complication rates between two groups. The secondary endpoints were to compare PSM, BCR and UC rates. Results: Both groups were statistically similar in terms of demographics and variables about PCa. Mean prostate volume was higher in Group 1 vs. Group 2 (69± 31 vs. 56±23 mL, p<.001). Total operative time was longer in Group 1 vs. Group 2 (144±38 vs. 136±44 min, p=.01). Biochemical recurrence, PSM, perioperative and postoperative complication rates of our population were 13.6%, 14.9%, 1.7% and 8.7%, respectively. There were no statistical differences in terms of perioperative complication, PSM and BCR rates between the groups(p>0.05). At the first month after RARP, total continence rate was statistically significant lower in Group 1 vs. Group 2 (49.2% and 56.5%, p=.03), respectively. However, there were no significant differences in terms of continence rates at 3rd month, 6th month and 1st-year follow-up. Conclusions: Due to our experience, the presence of ML does not seem to affect perioperative complication, intraoperative blood loss, PSM and BCR following RARP. However, the presence of ML seems to be a disadvantage in gaining early UC following RARP.